2015
DOI: 10.1371/journal.pone.0142406
|View full text |Cite
|
Sign up to set email alerts
|

The Retinoblastoma Tumor Suppressor Transcriptionally Represses Pak1 in Osteoblasts

Abstract: We previously characterized the retinoblastoma tumor suppressor protein (Rb) as a regulator of adherens junction assembly and cell-to-cell adhesion in osteoblasts. This is a novel function since Rb is predominantly known as a cell cycle repressor. Herein, we characterized the molecular mechanisms by which Rb performs this function, hypothesizing that Rb controls the activity of known regulators of adherens junction assembly. We found that Rb represses the expression of the p21-activated protein kinase (Pak1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Transcriptional and post-transcriptional regulations of each PAK present differences that may also change the way mutations affect brain development and functions. PAK1 expression is activated via FOXO and E2F2 transcription factors and is inhibited by Rb (de la Torre-Ubieta et al, 2010;Sosa-García et al, 2015). PAK2 transcriptional regulation is still an understudied subject, however, PAK2 was found as differentially methylated in children with ASD (Jasoliya et al, 2022).…”
Section: Pak Expression Patterns and Mutation Pathogenicitymentioning
confidence: 99%
“…Transcriptional and post-transcriptional regulations of each PAK present differences that may also change the way mutations affect brain development and functions. PAK1 expression is activated via FOXO and E2F2 transcription factors and is inhibited by Rb (de la Torre-Ubieta et al, 2010;Sosa-García et al, 2015). PAK2 transcriptional regulation is still an understudied subject, however, PAK2 was found as differentially methylated in children with ASD (Jasoliya et al, 2022).…”
Section: Pak Expression Patterns and Mutation Pathogenicitymentioning
confidence: 99%
“…Another ATP competitive inhibitor in our custom compound library, FRAX486, has strong activity against PAK1-3, and although some activity was detected against PAK4 it was much less potent [ 28 , 29 ]. Our previous work has shown that PAK1 (p21-activated kinase 1) is regulated by Rb [ 30 ]. Analysis of the PAK6 promotor sequence shows binding sites for E2F suggesting regulation by Rb as well [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…E2Fs are also known to control transcription of genes referred to as non-classical targets whose functions are not directly involved in cell cycle progression (e.g. p21activated protein kinase, prolyl isomerase Pin1, neo-genin), (Andrusiak et al, 2011;Julian & Blais, 2015;Julian et al, 2016;Ryo et al, 2002;Sosa-Garcia et al, 2015). According to a classical cell cycle regulation model by retinoblastoma RB/E2F pathway, E2F1-3 factors released from pocket protein pRB upon its phosphorylation by cyclin G 1 -dependent kinase complexes (cyclin D/cdk4 and cyclin E/cdk2), transactivate transcription of target genes that mediate S phase entry (e.g.…”
Section: Introductionmentioning
confidence: 99%